2018
DOI: 10.3329/bjmb.v9i2.36690
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Level in Gestational Diabetes Mellitus in a Tertiary Care Hospital of Bangladesh

Abstract: Gestational diabetes mellitus (GDM) is characterized by glucose intolerance during pregnancy. GDM is associated with an increased incidence of congenital abnormalities usually aggravated by maternal magnesium deficiency. Magnesium is one of the essential trace elements for normal embryogenesis and foetal growth and its deficiency increases mortality and morbidity rate of mothers, embryos and neonates. The present study was undertaken to evaluate the association of serum magnesium with GDM in second and third t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Thus it could be concluded that assessment of serum magnesium level should be done in each gestational diabetes mellitus case to reduce incidence of complications related to magnesium and also for timely administration of intervention. 15 This study was also supported by previous study by Bardicef 18 , Takaya 19 , and Yinsong Wang 20 . They found that pregnant women with gestational diabetes mellitus had lower plasma magnesium level than normal pregnant women.…”
Section: Correlation Between Mean Magnesium Level With Gestational Diabetes Mellitussupporting
confidence: 84%
See 3 more Smart Citations
“…Thus it could be concluded that assessment of serum magnesium level should be done in each gestational diabetes mellitus case to reduce incidence of complications related to magnesium and also for timely administration of intervention. 15 This study was also supported by previous study by Bardicef 18 , Takaya 19 , and Yinsong Wang 20 . They found that pregnant women with gestational diabetes mellitus had lower plasma magnesium level than normal pregnant women.…”
Section: Correlation Between Mean Magnesium Level With Gestational Diabetes Mellitussupporting
confidence: 84%
“…21 Tasdemir also found that there were no statistically significant differences in serum magnesium concentration between healthy pregnant women and pregnant women with gestational diabetes mellitus. 15 Further, prospective study by Nabouli which includes 99 pregnant women found that serum magnesium concentration in pregnant women with gestational diabetes mellitus was lower than normal pregnant women (0.89 ± 0.1 mmol/L vs 0.92 ± 0.2 mmol/L). Yet, this founding is not statistically significant, p = 0.51.…”
Section: Correlation Between Mean Magnesium Level With Gestational Diabetes Mellitusmentioning
confidence: 95%
See 2 more Smart Citations